(untitled) (Research, Society and Development, 2023)
Attention to food problems in Indonesia is considered very important, because food is the largest expenditure in the household. there are 104,242 heads of households who depend on rice farming and horticulture, and 137,309 elderly people aged 18–60 years who work as registered farmers in Tulang Bawang district. The rice commodity agribusiness development strategy is prepared based on external results and an internal evaluation matrix. This research aimed to determining the appropriate strategy for the development of rice commodity agribusiness in Tulang Bawang Regency in increasing food security after the Covid-19 pandemic. The methodology uses the location of the research was carried out in the Tulang Bawang Regency. The type of data used is primary and secondary data. The methodology is, using the EFE (External Factor Evaluation) and IFE (Internal Factor Evaluation) matrices. After that, a SWOT (Strength Weakness Opportunities Threats) QSPM (Quantitative Strategic Planning Matrix) analysis was carried out. Alternative the market penetration and development strategy undertaken is the intensification of rice farming; synergy between farmers, entrepreneurs and the government; strengthening regional food policies that are pro-farmers; revitalization of agricultural facilities and infrastructure.